2021
DOI: 10.1002/acr2.11236
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Integrated Care Management Program to Uncover and Address Social Determinants of Health for Individuals With Lupus

Abstract: Objective We studied patients with systemic lupus erythematosus (SLE) enrolled in a nurse‐led, multihospital, primary care–based integrated care management program (iCMP) for complex patients with chronic conditions to understand whether social determinants of health (SDoH), including food insecurity, housing instability, and financial constraints, were prevalent in this population. Methods The academic hospital‐based iCMP enrolls the top 2% of medically and psychosocially complex patients identified on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Among rheumatic disease patients, there is higher morbidity and mortality rates in racial/ ethnic minorities and individuals of lower socioeconomic status [26][27][28]. Importantly, social determinants of health affect quality of care and access that ultimately define health outcomes in this population [29,30]. This finding is of particular concern as appropriate monitoring and reliable use of immune suppressive medications for systemic lupus erythematosus (SLE) can reduce risk of end-stage renal disease and premature coronary artery disease [4,31,32].…”
Section: Telemedicine Highlights Health Inequities During the Coronav...mentioning
confidence: 99%
“…Among rheumatic disease patients, there is higher morbidity and mortality rates in racial/ ethnic minorities and individuals of lower socioeconomic status [26][27][28]. Importantly, social determinants of health affect quality of care and access that ultimately define health outcomes in this population [29,30]. This finding is of particular concern as appropriate monitoring and reliable use of immune suppressive medications for systemic lupus erythematosus (SLE) can reduce risk of end-stage renal disease and premature coronary artery disease [4,31,32].…”
Section: Telemedicine Highlights Health Inequities During the Coronav...mentioning
confidence: 99%
“…Increased travel burden was associated with more missed appointments and medication nonadherence, particularly among Black patients with lupus, due to including reliance on caregivers, financial constraints, and physical limitations (70,71). In an integrated care management program, 66% of patients reported concerns about medication access, and 61% about unmet transportation needs (61%) (72). Specialist diagnosis in American Indian/Alaskan Native people with lupus increased the likelihood of quality care indicators, such as having SLE classification criteria documented, being tested for biomarkers of disease activity, and receiving treatment with hydroxychloroquine (73).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of an iCMP team–based model to care plans of high‐need, high‐cost patients with SLE mitigates these SDoH factors by connecting patients with additional resources (such as social work support), improving care coordination, and nurturing relationships and trust. For example, our group recently found that among our cohort of patients with SLE enrolled in the iCMP between 2012 and 2019, iCMP nurses addressed at least one SDoH need for 81% of patients in our cohort and connected 75% of patients with additional resources ( 21 ). Of note, the 37% reduction in ED visit rates among patients with SLE enrolled in the iCMP at our institution from 2012 to 2019 is much greater than the 6% reduction in ED visit rates among all patients enrolled in the iCMP at our institution from 2009 to 2014 ( 10 ).…”
Section: Discussionmentioning
confidence: 99%